'Blue Lives Matter' and the legacy of blackface minstrelsy. (July 2021) - Longazel, Jamie
This article situates the pro-police countermovement, 'Blue Lives Matter', within the legacy of blackface minstrelsy. An analysis of various 'racial performances' shows how, like its minstrel forbearers, the rebuttal to Black Lives Matter subscribes to a dual identity: envious, fetishistic 'love' of Black people on one hand, visceral contempt accompanied by often-violent fantasies on the other. It is argued that by racialising themselves as 'blue', the countermovement seeks to expropriate the virtue associated with racial victimisation and articulate their racial fantasies about how Black folks ought to be. The article concludes by arguing that critical analyses of policing should consider policing performances rather than just policing practices.